The Roles of Junctional Adhesion Molecules (JAMs) in Cell Migration - Wang, Junqi; Liu, Han (Frontiers in Cell and Developmental Biology, 2022)
The review briefly summarizes the role of the family of adhesion molecules, JAMs (junctional adhesion molecules), in various cell migration, covering germ cells, epithelial cells, endothelial cells, several leukocytes, and different cancer cells. These functions affect multiple diseases, including reproductive diseases, inflammation-related diseases, cardiovascular diseases, and cancers. JAMs bind to both similar and dissimilar proteins and take both similar and dissimilar effects on different cells. Concluding relevant results provides a reference to further research.